Associations of Sociodemographic Factors With Health-Related Social Networks Among Pre-migration Filipinos. Issue 8 (1st October 2020) - Maglalang, Dale Dagar; Castro, A. B. de; Gee, Gilbert; Sabbath, Erika L.; Tran, Thanh V.; Takeuchi, David T.
ABSTRACT: Social networks provide health information that is useful to prevent illness, promote health, and facilitate treatment for health problems. One understudied facet is which people in social networks provide health information. The present article fills a critical gap in the empirical literature by identifying which social networks are reported based on a premigrant's sociodemographic status that operate as their source of health information. Data were analyzed from the Health of the Philippine Emigrants Study (HoPES) ( n = 829) migrant sample. Findings indicated having high English proficiency and educational attainment reduces the likelihood of reporting no one in their network as a source of health information. Those who reported family/relatives are less likely to be younger, and those who reported friends are also less likely to be living-in with a partner. This article informs social work researchers and practitioners in implementing interventions among premigration immigrants to help increase and broaden their social networks.